Intramolecular Force Field of Tetrazine Molecule - Mohan, S.; Vasuki, G.; Madivanane, R. (Asian Journal of Chemistry, 2010)
An orthonormalised set of symmetry coordinates, satisfying the transformation properties has been constructed for s-tetrazine molecule. With the help of Wilson's FG matrix method and using the molecular kinetic constants, a set of potential constants have been obtained. The other constants, namely, compliance constants, mean amplitudes of vibration, Coriolis coupling constants and centrifugal distortion constants have also been evaluated for the first time in the present work.